1856 Mass. Acts 86, An Act to Incorporate the Proprietors of Oak Grove Cemetery, ch. 154 § 6 - (:unkn) unknown (General Publisher, 1856)
Any person who shall . . . discharge any gun or other fire-arms, within the said limits, shall be deemed guilty of a misdemeanor, and upon conviction thereof before any justice of the peace, or other court of competent jurisdiction, shall be punished by a fine not less than five dollars, nor more than one hundred dollars...
--
Keywords: DISCHARGE